Da'wah Through Cultural Acculturation - Susana, Rina Rahadian (STAI AL-FALAH CICALENGKA, 2023)
The clash and resistance with local cultures forced Islam to find a symbol that was in line with the cultural capture capabilities of the local community. Islam's ability to adapt to local culture makes it easier for Islam to penetrate the lowest levels of society. As a result, Islamic culture was greatly influenced by peasant culture and inland culture, so that Islamic culture experienced a transformation not only because of the geographical distance between Arabia and Indonesia, but also because there were cultural distances. This process of cultural compromise certainly carries quite a few risks, because in certain circumstances it often tolerates interpretations that may deviate somewhat from pure Islamic teachings. This research aims to determine the relationship between da'wah and local culture and the negotiation of Islam with local culture. The research results show that the character of Indonesian Islam which dialogues with community traditions is accommodating to community traditions or local community culture rather than eradicating local community practices. Islam and societal traditions are placed in an equal position to have creative dialogue so that one of them is not in a subordinate position, which results in mutually weakening attitudes. This combination of Islam and community traditions is a richness of local interpretation so that Islam does not appear empty of true reality. Islam does not have to be perceived as Islam in Arabia. Keywords: Indonesian culture, Islam, tradition, transformation. Abstrak Benturan dan resistensi dengan kebudayaan-kebudayaan setempat memaksa Islam untuk mendapatkan simbol yang selaras dengan kemampuan penangkapan kultural dari masyarakat setempat. Kemampuan Islam untuk beradaptasi dengan budaya setempat, memudahkan Islam masuk ke lapisan paling bawah dari masyarakat. Akibatnya, kebudayaan Islam sangat dipengaruhi oleh kebudayaan petani dan kebudayaan pedalaman, sehingga kebudayaan Islam mengalami transformasi bukan saja karena jarak geografis antara Arab dan Indonesia, tetapi juga karena ada jarak-jarak kultural. Proses kompromi kebudayaan seperti ini tentu membawa resiko yang tidak sedikit, karena dalam keadaan tertentu seringkali mentoleransi penafsiran yang mungkin agak menyimpang dari ajaran Islam yang murni. Penelitian ini bertujuan untuk mengetahui relasi dakwah dan budaya lokal dan negosiasi Islam dengan budaya lokal. Hasil penelitian menunjukkan bahwa karakter Islam Indonesia yang berdialog dengan tradisi masyarakat bersikap akomodatif terhadap tradisi masyarakat atau kultur masyarakat setempat ketimbang memberantas praktik-praktik lokal masyarakat. Islam dan tradisi masyarakat ditempatkan dalam posisinya yang sejajar untuk berdialog secara kreatif agar salah satunya tidak berada dalam posisi yang subordinat, yang berakibat pada sikap saling melemahkan. Perpaduan antara Islam dengan tradisi masyarakat ini adalah sebuah kekayaan tafsir lokal agar Islam tidak tampil hampa terhadap realitas yang sesungguhnya. Islam tidak harus dipersepsikan sebagai Islam yang ada di Arab. Kata kunci: budaya Indonesia, Islam, tradisi, transformasi.